From inception to innovation: bibliometric analysis of the evolution, hotspots, and trends in implantable collamer lens surgery research - Zhang, Qing; Gong, Di; Li, Kunke; Dang, Kuanrong; Wang, Yun; Pan, Changfeng; Yan, Zonghui; Yang, Weihua (Frontiers in Medicine, 2024)
Background As one of several refractive surgeries, Implant Collamer Lens (ICL) surgery offers stable biocompatibility and consistent, high-quality visual outcomes. ICL has become an effective complement to corneal refractive surgery, gradually becoming one of the mainstream methods for correcting refractive errors. This study employs bibliometric methods to analyze research on ICL surgery to understand the progress, hotspots, and potential future trends in this field. Methods This study performed a bibliometric analysis of all ICL-related articles collected from the Web of Science Core Collection database between January 1st, 1996, and December 31st, 2023. The CiteSpace 6.2.R4 tool, Excel and the Web of Science website were used to analyze data by country, institution, keywords, and clusters of keywords. Additionally, an in-depth interpretation and analysis were conducted on the field’s high-impact articles. Results Since the first clinical application report of ICL, there have been a total of 875 studies. The number of papers published annually has shown an overall increasing trend. Studies published from China are the most numerous, accounting for 29.14% (n = 255) of the total. Among the institutions, Fudan University and Kitasato University both have published more than 50 papers, with Kitasato University having the highest H-index of 26. The journals with the top 10 publication volumes are all specialized in ophthalmology. The burst keywords since the introduction of ICL surgery have been “intraocular lens,” “refractive surgery,” and “cataract surgery.” The current burst keywords include “visual quality,” “vector analysis,” “axial length,” etc. The results of keyword clustering included ICL, pIOL, high myopia, axial length, optical quality, refractive surgery, ICL implantation, and pupil size. In the High-impact Articles, it was found that the high-impact articles predominantly focus on the safety, efficacy, and predictability of ICL surgery. Conclusion Research on ICL has grown since its clinical introduction, with the advent of the central hole ICL sparking a surge in recent hotspots, particularly in China. Current hotpots in the field of ICL surgery are “visual quality,” “ICL implantation,” “vector analysis,” “axial length,” “evo ICL,” “ICL v4c,” and “ICL.” ICL surgery research trends have evolved from implantation techniques to biological parameters associated with ICL surgery and the benefits of new ICL designs.